HORTICULTURAL PRODUCT DISTRIBUTION RISK MITIGATION BASED ON ENTERPRISE RISK MANAGEMENT (ERM) METHOD - Himmatul Miftah; Arti Yoesdiarti; Santia Afandi; Vigia Marfu’ah Zuher; Tiara Amanda Lestari; Ikhsan Qodri Pramartaa (Jurnal Sosial Humaniora, 2022)
Horticultural products of tomatoes and papayas are very susceptible to the risk of physical damage, weight loss and unsold so that they have the potential to cause losses. Potential losses can be reduced by identifying the risks that occur and mitigating the risks. This study aims to analyze the distribution risk and its mitigation in tomato and papaya horticultural products. Respondents were selected purposively and snowball sampling. Respondents identified were 40 respondents consisting of 17 retail respondents, 7 wholesale traders in the wholesale market, 7 middlemen respondents, and 9 farmers respondents. The results showed that the highest risk was at the farmer level and the smallest at the middleman level. Risk mapping consists of (1) weight loss at the level of farmers, middlemen, retailers and wholesalers in the wholesale market, respectively, having very low risk (Negligible) to moderate risk (Undesirable); (2) physical damage at the level of farmers, retailers, wholesalers in the wholesale market, farmers and middlemen respectively have very low to low risk categories; (3) unsold at the level of middlemen, farmers, retailers and wholesalers in the wholesale market, respectively, including the category of very low risk to moderate risk. Mitigation measures were carried out on weight loss in the form of making sorting warehouses, using tarpaulins for roofs, wrapping vegetables with newspapers. Mitigation actions for the risk of physical damage are carried out by applying fertilizers and pesticides as needed, making damage dependent agreements, supervising the sorting and picking process, wrapping vegetables with newspapers, closing stall with tarpaulins, and sending vegetables in the afternoon/evening. Mitigation actions for unsold risk are predicting demand trends, making purchase plans according to previous sales, and providing stock availability information. Keywords: ERM, distribution risk, weight loss, physical damage, mitigation